Human platelet-mediated cytotoxicity against Toxoplasma gondii: role of thromboxane (The Rockefeller University Press, 1991)
Human platelets, in the absence of antibody, are cytotoxic to tachyzoites of Toxoplasma gondii as determined by vital staining, transmission electron microscopy, and the failure of Toxoplasma to survive and replicate in mice after in vitro interaction of the organisms with platelets. Platelet to T. gondii ratios as low as 1:3 were toxic to the organisms with direct cell-cell contact essential for platelet-mediated cytotoxicity. Adherence of platelets to T. gondii and disruption of surface membranes and cytoplasmic contents of the organisms were observed ultrastructurally. Reactive oxygen species were not implicated in the platelet-mediated toxicity. The interaction of T. gondii with platelets resulted in a marked increase in thromboxane B2 (TXB2) production compared with that by unstimulated platelets. The cyclooxygenase inhibitors acetylsalicylic acid and indomethacin inhibited platelet-mediated cytolytic activity as did the selective TXA2 synthetase inhibitor dazmegrel, indicating a role for thromboxane in the platelet-induced cytotoxicity. Further, toxoplasmacidal activity was retained in the TXA2 synthetase-containing microsomal fractions of platelets disrupted by freezing and thawing; cytolytic activity was absent in microsome-depleted platelet supernatant fractions. Both the TXA2-generating platelet microsome system and a stable TXA2 analogue induced damage to the cellular membranes of the Toxoplasma as noted by transmission electron microscopy. These findings suggest that platelets may play a role in the host defense against Toxoplasma and that release of thromboxane may be important in this cytolytic process.